LEVEL OF READINESS AND ACCEPTANCE OF MAINSTREAM TEACHERS TOWARDS THE IMPLEMENTATION OF INCLUSIVE EDUCATION IN LEARNING DISABILITY (International Journal of Creative Future and Heritage (TENIAT), 2021)
AbstractInclusive Education Program (IEP) is a challenging educational transformation as the teachers who are involved in it need to equip themselves with a strong field of knowledge, sound teaching skills as well as commendable attitudes. This study aims to examine the state of readiness of mainstream teachers in terms of knowledge and acceptance of the implementation of the Inclusive Education Program for learning disabilities. A total of 80 mainstream teachers in several primary schools in the district of Kota Bharu Kelantan were selected as respondents in this study. Data were collected through an online survey using a google form questionnaire and were analyzed descriptively. The findings show that the involved mainstream teachers have a high level of state of readiness in terms of knowledge of the Inclusive Education Program, while in the aspect of acceptance, most respondents obtained a moderate level. The results of this study show that many efforts and programmes are needed to help improve knowledge and the level of acceptance among mainstream teachers to successfully implement an Inclusive Education Program for learning disability. AbstrakProgram Pendidikan Inklusif (Inclusive Education Programme, IEP) merupakan satu program transformasi Pendidikan negara yang mencabar kerana guru yang terlibat perlu melengkapkan diri dengan pengetahuan pendidikan inklusif yang mantap, kemahiran mengajar yang baik dan memiliki sikap yang terpuji. Kajian ini bertujuan untuk mengkaji tahap kesediaan guru arus perdana dari segi pengetahuan dan penerimaan pelaksanaan IEP dalam masalah pembelajaran. Seramai 80 orang guru arus perdana di beberapa sekolah rendah di daerah Kota Bharu, Kelantan telah dipilih sebagai responden kajian. Data dikumpulkan melalui kaedah tinjauan menggunakan borang soal selidik Google Form secara atas talian dan dianalisis secara deskriptif. Dapatan kajian menunjukkan guru arus perdana yang terlibat mempunyai tahap kesediaan yang tinggi dalam aspek pengetahuan berkaitan IEP, manakala dalam aspek penerimaan, majoriti responden menunjukkan tahap yang sederhana. Hasil kajian ini menunjukkan perlunya pelbagai usaha dan program dijalankan bagi membantu meningkatkan pengetahuan dan tahap penerimaan dalam kalangan guru arus perdana untuk melaksanakan IEP dalam kategori masalah pembelajaran.
Keywords: Inclusive Education; Learning Disability; Mainstream; Pendidikan Inklusif; Ketidakupayaan Pembelajaran; Arus Perdana